Winter sports - tourism activities in the Bâlea glacial area, Făgăraș massif (Southern Carpathians-Romanian Carpathians) - Florentina POPESCU (Editura Universităţii din Oradea, 2016)
Winter recreational activities (alpine skiing and touring ridges) are known in the Făgăraș massif since the end of the 18th century, and early of the 19th century. Due to terrain parameters (high elevations, favourable slopes) and climate (snowfalls and persistence of snow depth) Bâlea glacial area is famous for winter sports and tourism activities and for tourism infrastructure (cable car, several chalets and hotels and 2 points of Mountain Rescuer Public Services). Today, in contrast, off-piste skiing (freestyling and freeriding) is a younger and very popular sport activity. Therefore, skiing is only for experts and advances skiers. In recent years in the Bâlea glacial cirque, several forms of niche tourism were introduced: Church Ice and Ice Hotel and Inferno extreme skiing for skiers and snowboard competition. In the future heliskiing will develop, and for those who do not practice ski activities, snowmobile, paragladiders, photography.